2002
DOI: 10.1093/treephys/22.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene metabolism in Scots pine (Pinus sylvestris) shoots during the year

Abstract: Ethylene evolution, concentrations of 1-aminocyclopropane-1-carboxylic acid (ACC) and ACC conjugates, activities of ACC synthase and ACC oxidase, and cambial growth as measured by tracheid production were monitored from November to July in 1-year-old shoots, and between July and September in current-year shoots, of Scots pine (Pinus sylvestris L.). Needles, buds and four stem parts (cortex, phloem, cambial region and mature xylem) were surveyed. Ethylene evolution was quantified by gas chromatography. Free ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…3). This is in agreement with a number of studies in Norway spruce (Eklund 1990;Eklund et al 1992) and Scots pine (Ingemarsson et al 1991;Klintborg et al 2002) where it was shown that ethylene evolution is correlated to the period of most intense growth. Ethrel treatment of stem cambium in Picea abies (Eklund and Tiltu 1999) and Abies balsamea Little 1998, 2000) and ethylene gas treatment of cambium of Picea abies (Eklund and Tiltu 1999), Pinus taeda (Telewski 1990), and other pine species (Neel and Harris 1971) has also been shown to increase tracheid production.…”
Section: Discussionsupporting
confidence: 93%
“…3). This is in agreement with a number of studies in Norway spruce (Eklund 1990;Eklund et al 1992) and Scots pine (Ingemarsson et al 1991;Klintborg et al 2002) where it was shown that ethylene evolution is correlated to the period of most intense growth. Ethrel treatment of stem cambium in Picea abies (Eklund and Tiltu 1999) and Abies balsamea Little 1998, 2000) and ethylene gas treatment of cambium of Picea abies (Eklund and Tiltu 1999), Pinus taeda (Telewski 1990), and other pine species (Neel and Harris 1971) has also been shown to increase tracheid production.…”
Section: Discussionsupporting
confidence: 93%
“…In conifers, several endogenous roles have been established for the phytohormone ethylene. Ethylene has been correlated with cambial zone activity leading to xylem (wood) formation and diVerentiation (Ingemarsson et al 1991;Eklund and Little 1998;Little and Eklund 1999;Klintborg et al 2002). Previous studies have established a strong correlation between wounding, endogenous ethylene, and resin accumulation in conifers (Popp et al 1995;.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exogenous ethylene application can increase resin production and the number of resin ducts in several conifer species (Telewski et al 1983;Yamamoto and Kozlowski 1987;Katoh and Croteau 1997;. ACO activity, the Wnal step in ethylene formation, has previously been detected in several conifer species (Plomion et al 2000;Reynolds and John 2000;Klintborg et al 2002), but little is known about the corresponding ACO genes, their expression and cellular localization in conifers and the relationship of ACO with ethylene production and activities of specialized cells for phenolic or terpenoid formation after wounding in stems.…”
Section: Discussionmentioning
confidence: 99%
“…4e), suggesting that GAD activity is the major regulator of hypocotyl GABA levels during seedling development. To further characterize GAD in pine, we compared GAD expression with the expression of other genes encoding enzymes associated with seedling diVerentiation, including cytosolic NADP + -IDH (Palomo et al 1998;Pascual et al 2008), ascorbate peroxidase (APX), and oxidase (AOX) (Pignocchi and Foyer 2003;de Pinto and De Gara 2004), enzymes linked with ligniWcation and signaling, including laccase (LAC, Gavnholt and Larsen 2002), and 1-aminocyclopropane-1-carboxylic acid synthase (ACS), and oxidase (ACO), enzymes involved in ethylene synthesis that has been described to be connected to ligniWcation of plant stem (Klintborg et al 2002). Northern blots hybridized with speciWc probes indicated that these genes were diVerentially expressed in organs of pine seedlings (Fig.…”
Section: Gad Expression During Vascular Development In Pinementioning
confidence: 99%